2013
DOI: 10.1155/2013/308509
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Improved Detection and Management of Adult-Onset Hearing Loss in Australia

Abstract: Adult-onset hearing loss is insidious and typically diagnosed and managed several years after onset. Often, this is after the loss having led to multiple negative consequences including effects on employment, depressive symptoms, and increased risk of mortality. In contrast, the use of hearing aids is associated with reduced depression, longer life expectancy, and retention in the workplace. Despite this, several studies indicate high levels of unmet need for hearing health services in older adults and poor us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…These results provide evidence, at a community level, in support of results from studies of hearing-impaired individuals indicating that non-audiologic factors play a fundamental role in the early adoption of hearing rehabilitation and receptivity to hearing health care would be greater if delivered in a more integrated manner within the health-care setting (Meyer et al, 2014; Laplante-Levesque et al, 2012; McMahon et al, 2013). Other studies on determinants of hearing-aid acquisition and use have reported that education, occupation, and income disparities were significantly associated with hearing-aid use (Popelka et al, 1998; Bainbridge & Ramachandran, 2014; Nash et al, 2013; Fischer et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…These results provide evidence, at a community level, in support of results from studies of hearing-impaired individuals indicating that non-audiologic factors play a fundamental role in the early adoption of hearing rehabilitation and receptivity to hearing health care would be greater if delivered in a more integrated manner within the health-care setting (Meyer et al, 2014; Laplante-Levesque et al, 2012; McMahon et al, 2013). Other studies on determinants of hearing-aid acquisition and use have reported that education, occupation, and income disparities were significantly associated with hearing-aid use (Popelka et al, 1998; Bainbridge & Ramachandran, 2014; Nash et al, 2013; Fischer et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…It covers a wide range of aspects of hearing in old age, e.g. the influence of different life-style and health factors on hearing and the need for rehabilitation among elderly people (39)(40)(41)(42). There is also another study from South Australia (43).…”
Section: Studies From Other Parts Of the Worldmentioning
confidence: 99%
“…12 Various initiatives around the world, including Healthy People 2020 by the US Department of Health and Human Services and AHEAD III by the European Commission Framework Program, address the public health need of improving the detection of hearing impairment and the accessibility and implementation of its treatment. [13][14][15][16] Classical diagnostic audiometry involves a full diagnostic behavioral hearing test performed by a qualified audiologist at an appropriate facility. Most patients are referred for diagnostic audiometry by their primary care physician (PCP) following an office visit.…”
Section: Introductionmentioning
confidence: 99%